Analysis of Statistical Knowledge of Peruvian Medical Students: A Cross-Sectional Analytical Study Based on a Survey. - Vera-Ponce, V.J. (2022)
Introduction: Despite the growing awareness of the importance of knowledge in biostatistics, many investigations worldwide have found that medical students have a poor understanding of it. Objective: To determine the percentage of Peruvian medical students with sufficient biostatistics knowledge and the associated factors. Methods: Cross-sectional analytical study. Application of a virtual survey to medical students from different faculties in Peru. Results: 56.46% of medical students have insufficient knowledge of biostatistics. A statistically significant association was found for those who were 25 years of age or older (aPR: 1.195; 95% CI 1.045 - 1.366; p=0.009); being between the 9th and 12th semester (aPR: 1.177; 95% CI 1.001 - 1.378; p=0.037) and medical internship (aPR: 1.373; 95% CI 1.104 - 1.707; p=0.004); take an external course in biostatistics, epidemiology or research (aPR: 4.016; 95% CI 3.438 - 4.693; p<0.001); having read more than 12 articles per year (aPR: 1.590; 95% CI 1.313 - 1.967; p<0.001); and publish at least one scientific article (aPR: 1.549; 95% CI 1.321 - 1.816; p<0.001) or more than one (PR: 2.312; 95% CI 1.832 - 2.919; p<0.001). Conclusions: There is insufficient knowledge of biostatistics in medical students. The factors associated with a good understanding of this were age, academic semester, the number of articles read and published, and having taken an external course.